"Keep 'em in the East" Kazan, Kubrick, and the postwar New York film renaissance - Koszarski, Richard (Film and culture., 2021)
"Away from the glitz and glamour of Hollywood and the watchful eyes of the big studios, New York City re-emerged as a filmmaking center in the 1940s and 1950s. Filmmakers such as Elia Kazan, Sidney Lumet, Stanley Kubrick, and John Cassavetes built on their prior experience in theater, television, industrial films, and other aspects of the city's diverse cultural life, to create a film culture that would increasingly influence the financing, production and aesthetics of Hollywood films. Using on-location shooting to create a realistic, documentary style and relying on improvisatory practices, New York films had a distinct look and feel. Without studio financing, directors and producers raised funds and established independent production companies, creating the model that would go on to dominate Hollywood in the years to come. Richard Koszarski's magisterial history of the birth of independent cinema in New York City includes behind-the-scenes production histories of such iconic film as Kazan's On the Waterfront and Kubrick's The Killer's Kiss . The book also reveals the importance of "race films" in the history of New York City film. These all-black productions intended for African American audiences in urban ghettos and the rural South had been around New York City since the 1920s. They not only helped to keep the film business afloat in New York City but also nurtured and developed a core group of writers, directors, designers, and technicians that would become instrumental in the city's later growth as a center for filmmaking. New York's independent production companies also provided jobs for women that were not open to them in Hollywood. Finally, the book tells how Mayor O'Dwyer helped bring filmmaking to New York and how the relatively stable labor situation, particularly in comparison to Hollywood at the time, made New York a more hospitable place for directors"--